The role of chromogenic bacteria in external tooth discoloration in children - Zuhal Kırzıoğlu; Burcu Güçyetmez Topal (Gazi University, 2016)
Tooth discoloration can cause social and psychological problems and lead to loss of self-confidence in children. Concerns of parents and children on appearance and esthetics increase the importance of dental esthetic treatments in children. External tooth discoloration in children can be seen in both the primary and the permanent teeth. Poor oral hygiene, use of iron preparations and chromogenic bacteria are among the etiology of external tooth discoloration. Chromogenic bacteria can cause black/brown, green, orange or blue discolorations on the tooth surfaces of children. For clinicians, most interesting external tooth discoloration in children has been the black discoloration, which is more frequently observed compared to the other types. Most of the studies also have focused on the chromogenic bacteria associated with black discolorations, and the data concerning other types of discoloration are limited. Our knowledge on the existing chromogenic bacterial mechanisms is increasing by the developing microbiological diagnostic procedures, and new species associated with discoloration are becoming recognized. Still, studies dealing with the mechanisms of the chromogenic bacteria leading to discoloration are insufficient in the accessible sources. The objective of this article is to emphasize the role of the chromogenic bacteria in external tooth discoloration in children, to review precautions that can be taken to prevent discoloration, and current treatment methods, and to contribute to the current knowledge of the clinicians on this subject.